Anti-p200 Pemphigoid Mimicking Acquired Reactive Perforating Collagenosis - Janik Fleißner; Katrin Ickrath; Matthias Goebeler; Sandrine Benoit; Andreas Kerstan (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)